The role of the TRPV1 endogenous agonist N-Oleoyldopamine in modulation of nociceptive signaling at the spinal cord level - Spicarova, Diana; Palecek, Jiri (Journal of neurophysiology, 2009)
Transient receptor potential vanilloid (TRPV1) receptors are abundant in a subpopulation of primary sensory neurons that convey nociceptive information from the periphery to the spinal cord dorsal horn. The TRPV1 receptors are expressed on both the peripheral and central branches of these dorsal root ganglion (DRG) neurons and can be activated by capsaicin, heat, low pH, and also by recently described endogenous lipids. Using patch-clamp recordings from superficial dorsal horn (DH) neurons in acute spinal cord slices, the effect of application of the endogenous TRPV1 agonist N-oleoyldopamine (OLDA) on the frequency of miniature excitatory postsynaptic currents (mEPSCs) was evaluated. A high concentration OLDA (10 microM) solution was needed to increase the mEPSC frequency, whereas low concentration OLDA (0.2 microM) did not evoke any change under control conditions. The increase was blocked by the TRPV1 antagonists SB366791 or BCTC. Application of a low concentration of OLDA evoked an increase in mEPSC frequency after activation of protein kinase C by phorbol ester (PMA) and bradykinin or in slices from animals with peripheral inflammation. Increasing the bath temperature from 24 to 34 degrees C enhanced the basal mEPSC frequency, but the magnitude of changes in the mEPSC frequency induced by OLDA administration was similar at both temperatures. Our results suggest that presumed endogenous agonists of TRPV1 receptors, like OLDA, could have a considerable impact on synaptic transmission in the spinal cord, especially when TRPV1 receptors are sensitized. Spinal TRPV1 receptors could play a pivotal role in modulation of nociceptive signaling in inflammatory pain.
Keywords: dopamin; bradykinin; signální transdukce; Dose-Response Relationship, Drug; metoda terčíkového zámku; vztah mezi dávkou a účinkem léčiva; Ganglia, Spinal; In Vitro Techniques; Animals, Newborn; Rats; Analysis of Variance; Bradykinin; Neurogenic Inflammation; TRPV Cation Channels; Disease Models, Animal; Rats, Wistar; mužské pohlaví; Signal Transduction; techniky in vitro; novorozená zvířata; Patch-Clamp Techniques; analýza rozptylu; forbolové estery; krysa rodu Rattus; Excitatory Postsynaptic Potentials; měření bolesti; Pain Measurement; Phorbol Esters; Sensory Receptor Cells; excitační postsynaptické potenciály; modely nemocí na zvířatech; neurogenní zánět; zvířata; Temperature; kationtové kanály TRPV; Cinnamates; spinální ganglia; vazodilatancia; Dopamine; Vasodilator Agents; nervové receptory; Spinal Cord; anilidy; potkani Wistar; cinnamáty; mícha; Anilides; teplota; Male; Animals